2013
DOI: 10.1016/j.eats.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Augmentation With Subscapularis Tendon in Anterior Shoulder Instability With Capsulolabral Deficiency

Abstract: The treatment of chronic shoulder instability with poor quality of the anterior capsulolabral tissue is still controversial. In these cases the Latarjet procedure is certainly more effective in preventing recurrence than an arthroscopic capsular repair. However, several studies have reported a variety of severe complications related to the Latarjet procedure because of the use of bone augmentation and hardware implantation; moreover, the arthroscopic version of the Latarjet procedure is technically difficult a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“… 35 The sling effect of the upper subscapularis tenodesis was described, 47 and its function as an anterior barrier in recentering the humeral head was shown in a biomechanical study on specimens. 38 In a contemporary publication of a multicenter study, the reproducibility of this combination of the Bankart repair and the ASA technique was confirmed showing good results relative to failures without compromising external rotation. 36 …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“… 35 The sling effect of the upper subscapularis tenodesis was described, 47 and its function as an anterior barrier in recentering the humeral head was shown in a biomechanical study on specimens. 38 In a contemporary publication of a multicenter study, the reproducibility of this combination of the Bankart repair and the ASA technique was confirmed showing good results relative to failures without compromising external rotation. 36 …”
Section: Discussionmentioning
confidence: 86%
“…The upper third of the subscapularis tendon—as described in the Maiotti technique 38 —is usually fixed at 3 (R) or 9 (L) o'clock positions on the glenoid neck. In this technique, the tenodesis bone holes are placed on the anterior glenoid edge in an upper position, slightly over the top of the glenoid edge (at 10 o'clock in the left shoulders and 2 o'clock in the right shoulders), to avoid possible interference with the upper glenoid tunnel used for the fixation of the graft ( Fig 13 ).…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…However, especially in patients with multiple recurrences or previous procedures, the anteroinferior capsulolabral complex is often very stretched or deficient, putting in doubt the effectiveness of these reconstructions. 4 , 5 In addition, cadaveric and biomechanical studies have shown that capsular repair is not necessary to achieve the desired stability with the Latarjet procedure. 6 , 7 …”
mentioning
confidence: 99%
“…In cases in which a repair is not possible, few options remain for the treatment of these patients. Several surgical techniques, both nonanatomic 6 and anatomic, 7 , 8 , 9 , 10 , 11 have attempted to reconstruct the anterior glenohumeral capsule and the subscapularis muscle in this context. The results have varying rates of success and may be associated with altered biomechanics, high retear rates, and complications such as nerve injury.…”
mentioning
confidence: 99%